Bunites distigma (Brullé, 1837): discovery of the second- and third-instar larvae and phylogenetic relationships within the Colymbetinae (Coleoptera: Dytiscidae) - Michat, Mariano C.; Alarie, Yves; Balke, Michael (Zootaxa, 2023)
The second- and third-instar larvae of the diving beetle Bunites distigma (Brullé, 1837) are described and illustrated for the first time, including detailed morphometric and chaetotaxic analyses of selected structures, and their phylogenetic relationships within the Colymbetinae are re-evaluated. The results support previous hypotheses on the position of this genus based on first-instar characters, as Bunites Spangler, 1972 shares a common origin with Meladema Laporte, 1835, Hoperius Fall, 1927 and Neoscutopterus J. Balfour-Browne, 1943, and within this clade, it is sister to Meladema. Instars II and III of Bunites differ from other colymbetine genera by the presence of a basal suture on the urogomphi combined with the presence of posteroventral secondary setae on the protarsus. Some information on the habitat of the species is also provided.